Gastric Mucosal Microarchitectures Associated with Irreversibility with Helicobacter pylori Eradication and Downregulation of Micro RNA (miR)-124a. (21st October 2019) - Tahara, Tomomitsu; Tahara, Sayumi; Horiguchi, Noriyuki; Kawamura, Tomohiko; Okubo, Masaaki; Nagasaka, Mitsuo; Nakagawa, Yoshihito; Shibata, Tomoyuki; Urano, Makoto; Tsukamoto, Tetsuya; Kuroda, Makoto; Ohmiya, Naoki
Abstract: To investigate the molecular mechanisms of gastric carcinogenesis after Helicobacter pylori ( H. pylori ) eradication, expression of miR-124a, miR-34b, and miR-34c was examined in nonneoplastic gastric specimens after successful H. pylori eradication. The magnifying narrow-band imaging (NBI) endoscopic features of gastric mucosa were also examined. The atrophic type, an informative endoscopic feature for histological intestinal metaplasia, showed lower expression of miR-124a. Lower expression of miR-124a correlated with hypermethylation of the miR-124a3 locus. The atrophic type represents gastric microarchitectures associated with irreversibility with H. pylori eradication and downregulation of miR-124a.